2000
DOI: 10.2170/jjphysiol.50.77
|View full text |Cite
|
Sign up to set email alerts
|

Effective Arterial Elastance of Irregular Beats during Atrial Fibrillation in Canine Left Ventricle.

Abstract: ) was originally defined as the end-systolic pressure (ESP)/stroke volume (SV) ratio of the left ventricle (LV) [1][2][3]. E a is approximately equal to heart rate (HR) times total peripheral resistance (TPR) under stable hemodynamics [1][2][3]. E a has the same dimensions as an index of ventricular contractility (E max ) defined as the ESP/endsystolic volume (ESV) ratio [1][2][3][4][5][6]. E a proved to be powerful in evaluating the ventriculo-arterial coupling from the viewpoint of cardiac mechanoenergetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 27 publications
2
32
1
Order By: Relevance
“…We have found that not only RR, but also E max , E a , and ventriculo-arterial coupling (E a /E max ) distributed nonnormally with considerable skewness (lack of symmetry of a frequency distribution) and kurtosis (peakedness or flatness of a frequency distribution) [14]. Their meanϮSD values could not uniquely characterize their nonnormal frequency distributions [14], unlike a normal frequency distribution [15,16].We recognized in the present study the necessity of isovolumic contractions to scrutinize the frequency distributions of E max during AF for the following reason. Although E a and E a /E max require ejecting contractions whether in situ or ex vivo [13,14,17] Key words: arrhythmia, statistics, histogram, normality, variance.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…We have found that not only RR, but also E max , E a , and ventriculo-arterial coupling (E a /E max ) distributed nonnormally with considerable skewness (lack of symmetry of a frequency distribution) and kurtosis (peakedness or flatness of a frequency distribution) [14]. Their meanϮSD values could not uniquely characterize their nonnormal frequency distributions [14], unlike a normal frequency distribution [15,16].We recognized in the present study the necessity of isovolumic contractions to scrutinize the frequency distributions of E max during AF for the following reason. Although E a and E a /E max require ejecting contractions whether in situ or ex vivo [13,14,17] Key words: arrhythmia, statistics, histogram, normality, variance.…”
mentioning
confidence: 91%
“…However, the minimal number of beats from which the mean RR has been reliably obtained varied widely between only 4 beats to as many as the number of beats for 2 min among investigators and their purposes [9][10][11]. In some of these studies, mean RR was obtained to characterize the average RR even either in case of the nonnormal distribution or without testing its normality [1,5,6,[8][9][10][11].We have recently studied the frequency distributions not only of RR, but also of ventricular contractility (E max ) [12] and effective arterial elastance (E a ) [13] in in situ ejecting left ventricles during AF [14]. We have found that not only RR, but also E max , E a , and ventriculo-arterial coupling (E a /E max ) distributed nonnormally with considerable skewness (lack of symmetry of a frequency distribution) and kurtosis (peakedness or flatness of a frequency distribution) [14].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…EW), EDV, and ESP also fluctuated simultaneously. As for these fluctuations under AF, we have already analyzed them in detail [4,5,8,[12][13][14][15]. Figure 2 plots LV EW (open circles) and its efficiency (solid circles) against the predicted LV VO 2 of arrhythmic beats for 30 s in one canine heart.…”
Section: Statistical Analysesmentioning
confidence: 99%